Caspofungin modulates ryanodine receptor-mediated calcium release in human cardiac myocytes - Koch, Christian; Uhle, Florian; Weigand, Markus A. (Antimicrobial agents and chemotherapy, 2018)
Recent studies showed that critically ill patients might be at risk for hemodynamic impairment during caspofungin (CAS) therapy. The aim of our present study was to examine the mechanisms behind CAS-induced cardiac alterations. We revealed a dose-dependent increase in intracellular Ca2+ concentration ([Ca2+]i) after CAS treatment. Ca2+ ions were found to be released from intracellular caffeine-sensitive stores, most probably via the activation of ryanodine receptors.